International study of video review of concussion in professional sports. Issue 20 (27th September 2018) - Davis, Gavin A; Makdissi, Michael; Bloomfield, Paul; Clifton, Patrick; Echemendia, Ruben J; Falvey, Éanna Cian; Fuller, Gordon Ward; Green, Gary; Harcourt, Peter Rex; Hill, Thomas; McGuirk, Nathan; Meeuwisse, Willem; et al.
Abstract : Background: Video review has become an important tool in professional sporting codes to help sideline identification and management of players with a potential concussion. Aim: To assess current practices related to video review of concussion in professional sports internationally, and compare protocols and diagnostic criteria used to identify and manage potential concussions. Methods: Current concussion management guidelines from professional national and international sporting codes were reviewed. Specific criteria and definitions of video signs associated with concussion were compared between codes. Rules and regulations adopted across the codes for processes around video review were also assessed. Results: Six sports with specific diagnostic criteria and definitions for signs of concussion identified on video review participated in this study (Australian football, American football, world rugby, cricket, rugby league and ice hockey). Video signs common to all sports include lying motionless/loss of responsiveness and motor incoordination . The video signs considered by the majority of sports as most predictive of a diagnosis of concussion include motor incoordination, impact seizure, tonic posturing and lying motionless. Regulatory requirements, sideline availability of video, medical expertise of video reviewers and use of spotters differ across sports and geographical boundaries. By and large, these differences reflect a pragmatic approach from each sport, with limited underlying research and development of the video review process in some instances. Conclusions: The use of video analysis in assisting medical staff with the diagnosis or identification of potential concussion is well established across different sports internationally. The diagnostic criteria used and the expertise of the video review personnel are not clearly established, and research efforts would benefit from a collaborative harmonisation across sporting codes.